Implementasi Policy Base Routing Dan Failover Menggunakan Router Mikrotik Untuk Membagi Jalur Akses Inter Di Fakultas Komputer Universitas Bina Insan Lubuklinggau - armanto armanto (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2019)
ABSTRACT The problem in this study is that more and more internet users in the Bina Insan Lubuklinggau University building specifically the Faculty of Computer internet connection often experience problems, the internet network is still unstable, and ways to divide internet access points in the Computer Faculty. This study uses data collection methods by observing and recording directly at the research site (Observation), conducting question and answer directly to the source (Interview), and documentation by reading literature books. The results showed that the internet is often experiencing constraints and unstable internet networks and ways to divide internet access points at the Computer Faculty of the University of Bina Insan Lubuklinggau by using Policy Base Routing and Failover Implementation using a Mikrotik Router. It can be concluded that the internet network connection is stable and shows the results of the distribution of internet access points at the Faculty of Computer Bina Insan Lubuklinggau.